Zircon U-Pb strain chronometry reveals deep impact-triggered flow - Moser, D.; Davis, W.; Reddy, Steven; Flemming, R.; Hart, R. (Elsevier, 2009)
Large (>100km) meteorite impact cratering events play important roles in surface and biosphere evolution, however, their potential for widespread ductile modification of the lithosphere has been difficult to assess, due partly to our inability to isotopically age-correlate deep mineral fabrics with surface records. We have integrated benchmark U-Pb zircon dating methods (ID-TIMS, SHRIMP) with new microstructural techniques (EBSD, XRD) to demonstrate that crystal-plastic deformation can cause rapid out-diffusion of radiogenic Pb and accompanying trace element alteration in crystalline zircon. We have used this phenomenon to directly date fabric in Archean zircons and xenoliths of the lower crust of South Africa at 2023 15 million years, coeval with the 2020 3 million year old Vredefort cratering event at surface, with extent > or =20,000 km2. Our findings indicate that regional exogenic fabrics, similar to high-temperature tectonic fabrics, exist in ancient crust. Moreover, our results establish that crystal-plastic deformation in the lithosphere can now be directly dated and linked to planetary evolution by zircon U-Pb strain chronometry.